The impact of foreign direct investment on economic development in South Asia and Southeastern Asia - Darlington Chizema (Economies, 2025)
This study examines the impact of inward foreign direct investment (FDI) on economic growth in South and Southeast Asia from 2006 to 2022, using a comprehensive panel dataset and multiple econometric techniques. The baseline estimation employs Feasible Generalized Least Squares (FGLS), with robustness checks using Fixed Effects with Driscoll-Kraay standard errors, the Common Correlated Effects Mean Group (CCEMG) estimator, and Two-Stage Least Squares (2SLS). The results consistently show that FDI and Gross Capital Formation (GCF) significantly promote growth, while the Human Capital Index (HCI), Trade Openness (TO), and Inflation (I) have limited or adverse effects. Government spending (GS) is negatively associated with growth, suggesting inefficiencies in public resource allocation. The findings underscore the importance of enhancing absorptive capacity through investments in education, institutional quality, and trade facilitation. Policy recommendations include adopting performance-based budgeting and independent audits, drawing on Malaysia's anti-corruption and audit reforms. To address the weak impact of human capital, this study advocates for expanding public-private partnerships in technical and vocational education, modelled on Singapore's SkillsFuture initiative. Additionally, digital investment platforms like Indonesia's Online Single Submission (OSS) system and infrastructure upgrades are recommended to reduce trade costs and improve the investment climate. Finally, the study calls for deeper regional integration through harmonized investment regulations under the ASEAN Comprehensive Investment Agreement (ACIA) and the development of cross-border special economic zones (SEZs). These recommendations are grounded in empirical evidence and tailored to the region's structural characteristics, offering actionable insights for policy-makers.
Keywords: 330; FDI; Feasible Generalized Least Squares (FGLS); economic growth; Asia